Establishment of Bukit Kayu Hitam as a Special Border Economic Zone (SBEZ): Global lessons - Najimudin, Muhammad Fadhlullah; Md Dahlan, Nuarrual Hilal; Md Nor, Mohd Zakhiri (e-IPH, 2020)
Special Economic Zones (SEZs) is one of the known mechanisms to attract Foreign Direct Investment (FDI). Nevertheless, there was a global mix reaction towards its successful implementation with a few operational failures, especially in the area of its legal framework. Therefore, this paper aim is to explore the success and failure experience to be a reference for the development of Special Border Economic Zone at Bukit Kayu Hitam using qualitative textual analysis. It finds that two significant issues in SEZs; regulatory/ legal framework, and development spill-over.